PENERAPAN PEMBELAJARAN MODEL KOOPERATIF TIPE TEAM-ASSISTED INDIVIDUALIZATION DI SMP - Wardah, Wardah (Jurnal Pembelajaran Prospektif, 2020)
The purpose of this study was to determine the effect of TAI type cooperative learning models on student learning outcomes in the material of curved side space in class VIII SMP Negeri 2 Sungai Pinyuh. The form of research used in this study is a real experimental research design with Randomized control group pretest posstest design. Based on data analysis, it can be concluded that: 1) the average student learning outcomes before being taught with conventional learning is 53.5 whereas with TeamAssisted Individualization (TAI) cooperative learning type is 45.73. So, before being taught conventional learning and cooperative learning the type of TAI is classified as moderate; 2) the average student learning outcomes after being taught with conventional learning is 69.25 while with cooperative learning the Team-Assisted Individualization (TAI) type is 78.28. So, after being taught conventional learning and TAI type cooperative learning it turns out that the average student learning outcomes are relatively high; 3) from calculations using the Mann-Whitney U test it was concluded that the 95% confidence level turned out to be that the learning outcomes of students who were given Team-Assisted Individualization (TAI) cooperative learning were better than those of students who were given conventional learning. The effect of the application of the Team-Assisted Individualization (TAI) type of cooperative learning to student learning outcomes in the Curved Side Space Building material in class VIII of SMP Negeri 2 Sungai Pinyuh is classified as moderate with an effect size value of 0.58.